2016
DOI: 10.1186/s12977-016-0237-1
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of HIV-1 infection and intestinal CD4+ T cell depletion ex vivo by gut microbes altered during chronic HIV-1 infection

Abstract: Background: Early HIV-1 infection is characterized by high levels of HIV-1 replication and substantial CD4 T cell depletion in the intestinal mucosa, intestinal epithelial barrier breakdown, and microbial translocation. HIV-1-induced disruption of intestinal homeostasis has also been associated with changes in the intestinal microbiome that are linked to mucosal and systemic immune activation. In this study, we investigated the impact of representative bacterial species that were altered in the colonic mucosa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
74
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(76 citation statements)
references
References 64 publications
1
74
0
1
Order By: Relevance
“…Laboratory and analytic methods used to profile the intestinal microbiomes were as described 26,32,33,35 .…”
Section: Methodsmentioning
confidence: 99%
“…Laboratory and analytic methods used to profile the intestinal microbiomes were as described 26,32,33,35 .…”
Section: Methodsmentioning
confidence: 99%
“…The role of ATRA in regulating tolerance and immunity via the modulation of regulatory and effector functions of CD4 + T cells, respectively, is well established (41) Considering the strategic location of Th17 cells at portal sites of HIV/SIV entry (6,24,27,28,63), as well as their important role in maintaining mucosal immunity homeostasis in the context of a complex microbiota (6,64,65), our results point to the potential beneficial use of mTOR inhibitors in preventing HIV infection/ persistence in gut-homing Th17 cells.…”
Section: Discussionmentioning
confidence: 99%
“…This group and others have also suggested that HIV-1 infection alters the gut microbiota of North American individuals in which Prevotella, a bacterial genus of the Bacteroidetes phylum, is significantly enriched (52,(57)(58)(59). Dillon and coworkers, for their part, have proposed that translocation of Prevotella species to mucosal tissues is significantly increased in HIV-1-infected subjects compared to uninfected individuals (5,52). Despite the heterogeneity in the composition of the gut microbiota, this high abundance of the Prevotella genus and its enhanced capacity to translocate to extraintestinal sites thus suggest the predominance of Gram-negative bacteria in GALT of HIV-1-infected persons.…”
mentioning
confidence: 97%
“…Increased intraepithelial calcium concentrations (6,7) and reduced sodium glucose cotransport (6) were suggested as factors implicated in abnormal epithelial cell differentiation and organization. Ineffective glucose uptake mediated by the HIV-1 protein Tat (8) and microtubule disruption induced by the viral protein gp120 (7) are also thought to play a dominant role in the high level of enterocyte apoptosis observed in HIV-1-infected individuals (5,9). When associated with villous atrophy (10), this intestinal barrier disorganization causes disruption of epithelial tight junctions, resulting in the entry of microbial products into the bloodstream (a phenomenon also known as microbial translocation) (5,(11)(12)(13)(14)(15).…”
mentioning
confidence: 99%
See 1 more Smart Citation